A synoptic analogue model for QPF of river Sabarmati basin - RAY , KAMALJIT; SAHU, M. L. (MAUSAM, 1998)
An attempt has been made to prepare a model for issuing semi quantitative precipitation forecast for river Sabarmati by synoptic analogue method. The model is based on 10 years (1986- 95) of data. The QPF issued by the model is verified with the WAR of years 1995 and 1996. The performance of model was good. This model can be used confidently for issue of QPF for Sabarmati basin.